A prospective randomised study of a rigid video‐stylet vs. conventional lightwand intubation in cervical spine‐immobilised patients. (26th August 2016) - Seo, H.; Kim, E.; Son, J. D.; Ji, S.; Min, S. W.; Park, H. P.
Summary: Compared with a lightwand which is used blind, Optiscope ™, a rigid video‐stylet, can provide direct imaging of airway structures, potentially offering improved conditions in cervical spine‐immobilised patients. We randomly assigned 168 patients who required cervical immobilisation during tracheal intubation to use of the Optiscope or the lightwand. The initial intubation success rate (95% CI) was 90 (82–95)% with the Optiscope and 87 (78–93)% with the lightwand (p = 0.626). Median (IQR [range]) intubation time was longer (19 (12–41 [5–195] s vs. 15 (8–29 [3–117] s; p = 0.016), and there were fewer scooping movements (1 (1–2 [0–9]) vs. 2 (1–3 [0–14]); p = 0.002) when using the Optiscope compared with the lightwand. The incidence of postoperative airway complications was similar in the two groups. The devices were equivalent with respect to initial intubation success rate but the Optiscope yielded slightly longer intubating times.